2015
DOI: 10.1016/j.advwatres.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently engineering pore-scale processes: The role of force dominance and topology during nonwetting phase trapping in porous media

Abstract: a b s t r a c tWe investigate trapping of a nonwetting (NW) phase, air, within Bentheimer sandstone cores during drainage-imbibition flow experiments, as quantified on a three dimensional (3D) pore-scale basis via x-ray computed microtomography (X-ray CMT). The wetting (W) fluid in these experiments was deionized water doped with potassium iodide (1:6 by weight). We interpret these experiments based on the capillary-viscosity-gravity force dominance exhibited by the Bentheimer-air-brine system and compare to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 42 publications
2
97
1
Order By: Relevance
“…Results from reservoir condition core-scale experiments consisting of three D-I cycles indicate that although measured pressure profiles and relative permeability are cycle dependent parameters, cycle number has no discernible impact on residual scCO 2 saturations [Saeedi et al, 2011]; a similar result was found by Li et al [2015], who measured initial-residual saturation levels over two D-I cycles in Berea sandstone and found that the results conformed to the expected monotonic trapping curve. In contrast, results from recent pore-scale studies have suggested that intermittent injection patterns, or cyclic injections similar to water-alternating-gas schemes, could be utilized to break up the scCO 2 plume and enhance residual trapping of scCO 2 [Herring et al, 2013[Herring et al, , 2015; cyclic injection schemes have also previously been suggested by researchers performing basin-scale simulations [Spiteri et al, 2005]. In contrast, results from recent pore-scale studies have suggested that intermittent injection patterns, or cyclic injections similar to water-alternating-gas schemes, could be utilized to break up the scCO 2 plume and enhance residual trapping of scCO 2 [Herring et al, 2013[Herring et al, , 2015; cyclic injection schemes have also previously been suggested by researchers performing basin-scale simulations [Spiteri et al, 2005].…”
Section: Introductionmentioning
confidence: 97%
“…Results from reservoir condition core-scale experiments consisting of three D-I cycles indicate that although measured pressure profiles and relative permeability are cycle dependent parameters, cycle number has no discernible impact on residual scCO 2 saturations [Saeedi et al, 2011]; a similar result was found by Li et al [2015], who measured initial-residual saturation levels over two D-I cycles in Berea sandstone and found that the results conformed to the expected monotonic trapping curve. In contrast, results from recent pore-scale studies have suggested that intermittent injection patterns, or cyclic injections similar to water-alternating-gas schemes, could be utilized to break up the scCO 2 plume and enhance residual trapping of scCO 2 [Herring et al, 2013[Herring et al, , 2015; cyclic injection schemes have also previously been suggested by researchers performing basin-scale simulations [Spiteri et al, 2005]. In contrast, results from recent pore-scale studies have suggested that intermittent injection patterns, or cyclic injections similar to water-alternating-gas schemes, could be utilized to break up the scCO 2 plume and enhance residual trapping of scCO 2 [Herring et al, 2013[Herring et al, , 2015; cyclic injection schemes have also previously been suggested by researchers performing basin-scale simulations [Spiteri et al, 2005].…”
Section: Introductionmentioning
confidence: 97%
“…At the pore scale, micro-CT technology has the capability to image the location of the residual phases inside the pore space, thus providing detailed information on the size and shape of the residual ganglia [17][18][19][20][21][22][23][24][25][26][27][28]. Another important application of the micro-CT imaging is the measurement of contact angle at reservoir conditions (elevated temperature and pressure) [29], which is one of the main input parameters for pore-scale numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…In order to devise models applicable to a range of capillary numbers, additional parameters describing the topology of the fluid subphases may be crucial. The topology of a fluid subphase can be described by the Euler characteristic, which has been used previously by Herring et al (2015) to study the 3D topology of the nonwetting fluid phase and its effect on nonwetting phase trapping. They found that for high capillary numbers, the nonwetting phase Euler number plays an important role on the residual nonwetting saturation.…”
Section: Discussionmentioning
confidence: 99%